Block Chain Assisted Document Updation using Positional Index Altering Scheme in Cloud Server: Asymmetric Searchable Encryption Approach - Dayanand Lal N., Beena G. Pillai (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Users have the option to share or use their data on the cloud. Cloud computing provides a great deal of convenience for users. However, it also brings up a number of security issues. Data owners may be unable to fully trust cloud servers and lose control over their data, which is one of the key security risks of cloud computing. One of the main issues with the existing system is security when changing files. Ensuring security during updates and encrypting the submitted material is the most significant problem. This paper presents an index-altering approach in Cloud Server that uses a Positional Index to facilitate blockchain-assisted document updating. In this situation, use a smart contract to utilize trustworthy cloud computing and Blockchain technologies. The work’s implementation of forward and backward privacy and document updating is its most crucial component. It also fends off both active and passive assaults. The Diffie–Hellman (DH) key exchange protocol, the Positional Index Altering Scheme, the Fuzzy duo Trapdoor key search, the Homographic Asymmetric El-Gamal encryption technique, and the Blockchain smart contract are the security features of the suggested scheme. In a decentralized search system, the entire evaluation is validated.